2005
DOI: 10.1111/j.1365-2796.2004.01443.x
|View full text |Cite
|
Sign up to set email alerts
|

Immune regulation of central nervous system functions: from sickness responses to pathological pain

Abstract: Classically, the central nervous system (CNS) and the immune system are thought to operate independently of each other. This simplistic view has been corrected in recent years, first with the recognition that the brain dynamically modulates the immune system, and later with the reverse; that is, that the immune system modulates the CNS as well. The evidence that the immune system regulates CNS functions is first reviewed. This immune-to-brain communication pathway triggers the production of a constellation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
231
2
5

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 321 publications
(256 citation statements)
references
References 148 publications
(201 reference statements)
11
231
2
5
Order By: Relevance
“…For example, PA treatment in adipocytes induced expression of interleukin‐6 and accumulation of reactive oxygen species 33. These inflammatory signals can be transmitted across the blood‐brain barrier by activation of glia cells and cumulate in the release of inflammatory cytokines 34. The resulting neuroinflammation increases oxidative stress, which changes neuronal membrane stability and affects catecholamine neurotransmission, a mechanism involved in traditional depressive pathophysiology 35.…”
Section: Discussionmentioning
confidence: 99%
“…For example, PA treatment in adipocytes induced expression of interleukin‐6 and accumulation of reactive oxygen species 33. These inflammatory signals can be transmitted across the blood‐brain barrier by activation of glia cells and cumulate in the release of inflammatory cytokines 34. The resulting neuroinflammation increases oxidative stress, which changes neuronal membrane stability and affects catecholamine neurotransmission, a mechanism involved in traditional depressive pathophysiology 35.…”
Section: Discussionmentioning
confidence: 99%
“…Besides signs of neuroinflammation as reflected by CSF cytokine indices, brain positron emission tomography (PET) scans of patients with chronic back pain show microglial cell specific activation (greater than healthy controls) in: 1) medial thalamic, 2) post central gyrus, and 3) paracentral lobule, suggesting that chronic pain mediated neuroinflammation and central sensitization likely co-occur in both the brain and spinal cord (Loggia et al, 2015). The mechanisms of central sensitization are known to involve neuronal interaction with activated glia cells and astrocytes (Milligan and Watkins, 2009;Watkins and Maier, 2005). Activated microglia and astrocytes release pro-inflammatory cytokines/chemokines such as TNF␣, IL-1␤, IL-6 and IL-8, in addition to glutamate and substance P, which collectively are known to amplify pain (Milligan and Watkins, 2009;Watkins and Maier, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms of central sensitization are known to involve neuronal interaction with activated glia cells and astrocytes (Milligan and Watkins, 2009;Watkins and Maier, 2005). Activated microglia and astrocytes release pro-inflammatory cytokines/chemokines such as TNF␣, IL-1␤, IL-6 and IL-8, in addition to glutamate and substance P, which collectively are known to amplify pain (Milligan and Watkins, 2009;Watkins and Maier, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Substantial evidence indicates dysregulation of the (neuro)immune system in both depression and chronic pain (for review see Miller et al, 2009, Watkins andMaier, 2005); which may also underlie the association between these conditions. Pre-clinical studies have demonstrated peripheral nerve injury-induced neuroimmune activation in brain regions responsible for the modulation of nociception and/or affect, including the prefrontal cortex (Apkarian et al, 2006, Al-Amin et al, 2011.…”
Section: Introductionmentioning
confidence: 99%